Spanish relief of the International Solidarity Fund (circular) - Stolz, George
028-0187-001 FÉDÉRATION SYNDICALE INTERNATIONALE INTERNATIONAL FEDERATION OF TRADE UNIONS INTERNATIONALER GEWERKSCHAFTSBUND 9, AVENUE D'ORSAY, PARIS - VIIe ADRESSE TÉLÉGRAPHIQUE: TELEGRAPHIC ADDRESS: TELEGRAMMADRESSE: INTERFED, PARIS TÉLÉPHONE: INVALIDES 45-88 St/H/G. Fonds int. de Solid. 133. 21st September, 1936. To Affiliated National Centres. To International Trade Secretariats. To Relief Committees. Dear Comrades, SPANISH RELIEF OF THE INTERNATIONAL SOLIDARITY FUND. On the 10th September, a delegation from the International Solidarity Fund, consisting of J. Stolz for the International Federation of Trade Unions and J. Delvigne for the Labour and Socialist International, accompanied by John Price, visited Madrid in order to organise relief work for Spain on the spot, in conjunction with representatives of the Spanish Movement. In agreement with the Spanish National Trade Union Centre (UGT) and the Spanish Socialist Party, it was decided to set up a Spanish Committee of the International Solidarity Fund, to which all contributions will be sent from the Fund and through which relief would be distributed. The Committee is composed of the Deputy Carlos Hernandez (for the Spanish National Trade Union Centre), and Enrique Santiago, Director of the Social Insurance Scheme (for the Socialist Party). The address of the Committee is: Carlos Hernandez Unión General de Trabajadores, Fuencarral 93, Madrid. Remittances should still be made payable to the "International Solidarity Fund" (Aid for Spain), Account No. 40258 of the International Federation of Trade Unions, Crédit Lyonnais, 2 bis Avenue Bosquet, Paris 7e. Contributions in kind, for the help of the needy, sick and wounded, such as medical supplies, clothing, imperishable food supplies, can also be made, but, in view of the transport difficulties and the fact that some consignments destined for Madrid or elsewhere have been detained in Barcelona and not transmitted, care must in this case be taken to choose a method and route which will assure safe delivery to the Spanish Committee. I should be glad to be notified of the despatch of consignments via France, whereupon I will at once inform you of the name and address of the firm dealing with shipping the cargo to Spain, it is of course understood that your organisation will bear the cost of transport to Marseilles. It should be noted that consignments sent by sea to the Madrid Committee must be sent via the port of Alicante, as this is the safest port and provides the most rapid communication, delivery in Madrid being made twelve hours after arrival in Alicante. Yours sincerely, G. Stolz, Assistant Secretary. 292/946/28/187